SMOKING POLICIES IN FEDERAL BUILDINGS A SURVEY BY THE OFFICE OF U.S. SENATOR FRANK R. LAUTENBERG (D-NJ) - LAUTENBERG,FR (Tufts Archival Research Center, 2007)
Press release of a survey on smoking policies in federal buildings. Breaks down buildings into legislative branch, executive branch, independent government agencies, and the judicial branch. Lists buildings under each category and briefly summarizes findings.